NADH plays the vital role for chiral pure D‐(−)‐2, 3‐butanediol production in Bacillus subtilis under limited oxygen conditions. Issue 10 (28th May 2014) - Fu, Jing; Wang, Zhiwen; Chen, Tao; Liu, Weixi; Shi, Ting; Wang, Guanglu; Tang, Ya‐jie; Zhao, Xueming
ABSTRACT Compared with traditional pathogenic producers, Bacillus subtilis as a Class I microorganism offers many advantages for industrial‐scale 2, 3‐butanediol production. Unlike previous reports in which two stereoisomers (with a ratio of 3:2) were produced, we first found that wild type B. subtilis 168 generates only D‐(−)‐2, 3‐butanediol (purity >99%) under low oxygen conditions. The total high yield of 2, 3‐butanediol and acetoin, and acetoin reductase enzyme assay indicate that it is the high level of NADH availability, instead of high acetoin reductase activity, contributes more to 2, 3‐butanediol production in B. subtilis. The strategy for increasing the pool of NADH availability, the key factor for 2, 3‐butanediol production, was designed through low dissolved oxygen control, adding reducing substrates and rationally metabolic engineering. A transhydrogenase encoded by udhA was introduced to provide more NADH from NADPH and allowed enhanced 2, 3‐butanediol production. Finally, BSF20 produced 49.29 g/L D(−)‐2, 3‐butanediol. These results demonstrated that B. subtilis is a competitive producer for chiral 2, 3‐butanediol production. Biotechnol. Bioeng. 2014;111: 2126–2131. © 2014 Wiley Periodicals, Inc.